FORMATION AND DEVELOPMENT OF LINGUOPOEICS AS A SECTION OF PHILOLOGY - Babakhanov Laziz Abdullahanovich (Web of Journals Publishing, 2024)
This work is devoted to the formation and development of linguopoetics as a new branch of philology, as well as its methodology. The purpose of the study is to try to establish whether linguopoetics is an independent philological discipline or whether it is a simple combination of linguistic stylistics and literary criticism.
Keywords: linguopoetics, philology, teaching, linguistics, discipline, poetics, linguistics.